Sensory processing disorder: Perceptions on the clinical role of advanced psychiatric nurses - Madelein Lang; Emmerentia du Plessis (AOSIS, 2019)
Background: No description of the clinical role of the advanced psychiatric nurse in the management of children with sensory processing disorder could be found for the South African context. This is a loss in clinical nursing practice with regard to diagnosis, treatment and research. Aim: To explore and clarify the perceptions of healthcare professionals in South Africa on the clinical role of the advanced psychiatric nurse in sensory processing disorder to provide a description of this role. Setting: The research was conducted by inviting registered healthcare professionals practicing in South Africa to complete several rounds of an on-line survey. Methods: An explorative and descriptive design was used. Purposive sampling was used to identify an initial sample of healthcare professionals, followed by snowball sampling. The Delphi technique was implemented with three sequential rounds, gathering data on the perceptions of the healthcare professionals regarding the clinical role of the advanced psychiatric nurse in sensory processing disorder. Results: The following main themes crystallised from the data - (1) Specialised training of the advanced psychiatric nurse (APN) on sensory processing disorder; (2) Interventions carried out by the APN with regard to sensory processing disorder; (3) Adequate support to the family with regard to sensory processing disorder; and (4) Referral of a child with sensory processing disorder. Conclusion: The study indicates that the healthcare professionals who are experts in delivering healthcare to children with sensory processing disorder agree that the APN with additional training in this condition has a clinical role to play in rendering healthcare to these healthcare users. A preliminary clinical role description could be formulated. Recommendations for nursing practice, nursing education and further research were formulated.